Changes in salivary biomarkers of oxidative status in calves at weaning and grouping - Camila Peres Rubio (BMC, 2021)
Abstract Background Saliva is being increasingly used as a sample for measuring biomarkers in several species and shows a high potential of use to detect and monitor stress. The weaning and grouping in dairy calves are a particularly stressful time. Therefore, the objectives of this study were to evaluate a panel of antioxidant and oxidant biomarkers in the saliva of calves on the day of weaning (W0), 2 days after weaning or milk withdrawal (W + 2), and 4 days after grouping (G + 4). In addition, to verify if cortisol and oxytocin concentrations are related to the biomarkers measured. Results Salivary cupric reducing antioxidant capacity (CUPRAC), ferric reducing ability of saliva (FRAS), Trolox equivalent antioxidant capacity (TEAC), advanced oxidation protein products (AOPP), and ferrous oxidation-xylenol orange (FOX) were significantly higher (P < 0.02) 4 days after grouping than the day of weaning and 2 days after. The increases were 50 and 54% for CUPRAC, 93 and 116% for FRAS, 117 and 135% for TEAC, 22 and 49% for AOPP and 10 and 5% for FOX in comparison with weaning and 2 days after, respectively. In addition, oxytocin and cortisol showed significant negative and positive correlations (P < 0.05) respectively with the biomarkers of oxidative status. Conclusions Our results showed that calves after grouping show increases in antioxidants and oxidants concentrations, indicating that a balance between these molecules has been tried to maintain during this stressful situation. The dynamic changes of biomarkers of oxidative status should be explored and characterised in other stressful conditions.